Social Influence on Evacuation Behavior in Real and Virtual Environments - Kinateder, Max; Warren, William H. (Frontiers in Robotics and AI, 2016)
Virtual reality (VR) is a promising tool to study evacuation behavior as it allows experimentally controlled, safe simulation of otherwise dangerous situations. However, validation studies comparing evacuation behavior in real and virtual environments are still scarce. We compare the decision to evacuate in response to a fire alarm in matched physical and virtual environments. 150 participants were tested individually in a one-trial experiment in one of three conditions. In the Control condition, the fire alarm sounded while the participant performed a bogus perceptual matching task. In the Passive bystander condition, the participant performed the task together with a confederate who ignored the fire alarm. In the Active bystander condition, the confederate left the room when the fire alarm went off. Half of the participants in each condition experienced the scenario in the real laboratory, and the other half in a matched virtual environment with a virtual bystander, presented in a head-mounted display. The active bystander group was more likely to evacuate, and the passive bystander group less likely to evacuate, than the control group. This pattern of social influence was observed in both the real and virtual environments, although the overall response to the virtual alarm was reduced; positive influence was comparable, whereas negative influence was weaker in VR. We found no reliable gender effects for the participant or the bystander. These findings extend the bystander effect to the decision to evacuate, revealing a positive as well as the previous negative social influence. The results support the ecological validity of VR as a research tool to study evacuation behavior in emergency situations, with the caveat that effect sizes may be smaller in VR.